Identifikasi Telur Cacing Soil Transmitted Helminths (Sth) Dengan Menggunakan Pewarna Alami Antosianin Dari Ubi Jalar Ungu - Islawati, Islawati; Arwie, Dzikra; Salnus, Subakir (Jurnal Medisains Kesehatan, 2024)
The purple color in sweet potatoes is caused by the presence of natural pigments known as anthocyanins. The concentration of anthocyanins varies among purple sweet potatoes, resulting in various shades of purple. Soil Transmitted Helminths (STH), commonly known as worms, are infectious diseases caused by intestinal nematode parasites transmitted through soil. This study aims to observe the effect of varying concentrations of anthocyanins extracted from purple sweet potato tubers in detecting STH eggs using the sedimentation method. This research uses laboratory experiments with categorical descriptive characteristics, varying the anthocyanin concentrations from purple sweet potatoes: 100%, 60%, 40%, 20%. The results showed that a 60% anthocyanin concentration can effectively serve as a substitute for 2% Eosin reagent in staining worm eggs. Thus, it can be concluded that a 60% concentration is optimal for staining worm eggs or as a natural dye alternative for worm egg staining.